A pilot study of the performance of captive‐reared delta smelt Hypomesus transpacificus in a semi‐natural environment. Issue 6 (6th November 2019) - Hung, Tien‐Chieh; Rosales, Marlin; Kurobe, Tomofumi; Stevenson, Troy; Ellison, Luke; Tigan, Galen; Sandford, Marade; Lam, Chelsea; Schultz, Andrew; Teh, Swee
Abstract: A captive breeding programme was developed in 2008 for delta smelt Hypomesus transpacificus in reaction to dramatic population decline over several decades. We took 526 sub‐adult captive‐reared delta smelt and cultured them for 200 days without providing artificial food or water quality management to assess their performance once released in the wild. The results indicated captive‐reared sub‐adult delta smelt could survive in a semi‐natural environment with uncontrolled water quality and naturally produced wild prey through spawning and into their post spawning phase.